Biomarkers and pathways of chemoresistance and chemosensitivity for personalized treatment of pancreatic adenocarcinoma - Zemanek, Tomas; Melichar, Bohuslav; Lovecek, Martin; Soucek, Pavel; Mohelnikova-Duchonova, Beatrice (Pharmacogenomics, 2019)
Pancreatic carcinoma is usually diagnosed late when treatment options are limited and is considered a chemo-resistant malignancy. However, early stage, good performance status and specific patient subgroup are thought to have a more favorable prognosis. Search for novel molecular biomarkers, which could predict treatment resistance, represents a major opportunity, but also a challenge in further research. This review summarizes most aspects of individualized therapy of pancreatic cancer including promising biomarkers, BRCA-deficient pancreatic cancer and its etiology. It may be estimated that nearly a third of metastatic pancreatic ductal adenocarcinoma patients could benefit from treatment other than gold standard chemotherapy. Thus, other aspects of an individualized approach concerning the main factors for the choice of the best therapy for individual pancreatic cancer patient (surgery and chemotherapy), as well as the future directions (target therapy and immunotherapy), are also addressed.
Keywords: PARP inhibitors; Drug Resistance, Neoplasm; resistance; individualizovaná medicína; therapy; Pancreatic Neoplasms; cílená molekulární terapie; lidé; Immunotherapy; nádory slinivky břišní; chemorezistence; signální transdukce; Antineoplastic Combined Chemotherapy Protocols; Signal Transduction; protokoly protinádorové kombinované chemoterapie; biomarker; Adenocarcinoma; nádorové biomarkery; imunoterapie; genomics; adenokarcinom; Biomarkers, Tumor; pancreatic ductal adenocarcinoma; Precision Medicine; BRCA; Molecular Targeted Therapy; Humans